MiR-375 is Essential for Human Spinal Motor Neuron Development and May Be Involved in Motor Neuron Degeneration. (20th November 2015) - Bhinge, Akshay; Namboori, Seema C.; Bithell, Angela; Soldati, Chiara; Buckley, Noel J.; Stanton, Lawrence W.
Abstract: The transcription factor REST is a key suppressor of neuronal genes in non-neuronal tissues. REST has been shown to suppress proneuronal microRNAs in neural progenitors indicating that REST-mediated neurogenic suppression may act in part via microRNAs. We used neural differentiation of Rest -null mouse ESC to identify dozens of microRNAs regulated by REST during neural development. One of the identified microRNAs, miR-375, was upregulated during human spinal motor neuron development. We found that miR-375 facilitates spinal motor neurogenesis by targeting the cyclin kinase CCND2 and the transcription factor PAX6. Additionally, miR-375 inhibits the tumor suppressor p53 and protects neurons from apoptosis in response to DNA damage. Interestingly, motor neurons derived from a spinal muscular atrophy patient displayed depressed miR-375 expression and elevated p53 protein levels. Importantly, SMA motor neurons were significantly more susceptible to DNA damage induced apoptosis suggesting that miR-375 may play a protective role in motor neurons.